2022
DOI: 10.1038/s41467-022-33442-2
|View full text |Cite
|
Sign up to set email alerts
|

Building up libraries and production line for single atom catalysts with precursor-atomization strategy

Abstract: Having the excellent catalytic performance, single atom catalysts (SACs) arouse extensive research interest. However, the application of SACs is hindered by the lack of versatile and scalable preparation approaches. Here, we show a precursor-atomization strategy to produce SACs, involving the spray of droplets of solutions containing metal precursors onto support surface through ultrasonic atomization and the subsequent calcination. This approach is versatile to successful synthesis of a series of catalysts, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…It is commonly accepted that the SACs’ coordination structures determine the electronic structures and thus affect the intrinsic electrocatalytic activity. It follows that the local/expanded coordination environment of active single atoms in SACs has a combined effect on the stability, catalytic performance, and utilization of the loaded materials [ 142 , 143 ]. As shown in Table 1 , asymmetric atom sites, which have recently gained popularity among a wide range of researchers, can provide flexible structures with customizable atomic configuration, local/expanded coordination, and electronic architecture without damaging this principle of high atomic utilization, thereby breaking such innate limitations of MN 4 .…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly accepted that the SACs’ coordination structures determine the electronic structures and thus affect the intrinsic electrocatalytic activity. It follows that the local/expanded coordination environment of active single atoms in SACs has a combined effect on the stability, catalytic performance, and utilization of the loaded materials [ 142 , 143 ]. As shown in Table 1 , asymmetric atom sites, which have recently gained popularity among a wide range of researchers, can provide flexible structures with customizable atomic configuration, local/expanded coordination, and electronic architecture without damaging this principle of high atomic utilization, thereby breaking such innate limitations of MN 4 .…”
Section: Discussionmentioning
confidence: 99%
“…SACs on molecularly defined supports are ideal targets for employing mass spectrometry techniques relying on soft ionization methods. We employed electrospray ionization mass spectrometry (ESI-MS) for the study of solubilized SACs supported on lacunary POMs such as PW 11 O 39 . When mixing equimolar amounts of Rh nitrate and PW 11 O 39 7– , we observed the quantitative formation of PW 11 O 39 Rh 1 4– in solution with seemingly complex but easily predictable cation envelopes (Figure a). As a first test example, we conducted mechanistic studies for CO oxidation by measuring the m/z values of the observed intermediates after sequential exposure to CO and O 2 .…”
Section: Sacs Supported On Molecularly Defined Oxidesmentioning
confidence: 99%
“…Single-atom catalysts (SACs) composed of atomically dispersed metal sites on support materials have sporadically been reported for various catalytic applications throughout the last century with the field seeing a rejuvenation since the report of Pt SACs active in room-temperature CO oxidation. , While SACs have shown promising catalytic activity in many classes of reactions, mostly ascribed to their unique electronic structure, highest possible metal dispersion and metal-supported interface area, SACs also hold potential in serving as model systems for the study of active sites. Determining the identity of catalytic active sites under reaction conditions could allow for the accurate study of their intrinsic activity and selectivity by experimental and computational means . Based on these insights, the rational design of catalytic materials comprising certain active sites becomes possible.…”
Section: Introductionmentioning
confidence: 99%
“…The k 3 -weighted Fourier-transform spectra from EXAFS (C) and normalized XANES spectra (D) at Pd K-edge. Reprinted from He et al (2022) . Copyright © 2022, with permission from Springer Nature.…”
Section: Characterizations Of Single-atom Catalysts For Air Pollutant...mentioning
confidence: 99%
“…For instance, on Pd1/FeO x , the normalized XANES spectra show that the absorption edge positions of Pd1/FeO x were between those of Pd foil and PdO, suggesting positively charged Pd species ( Figure 4D ). In EXAFS, two prominent peaks at ∼1.5 and ∼2.9 Å originate from the Pd-O and Pd-O-Fe coordination, respectively, and Pd-Pd scattering is absent, excluding the possibility of the existence of Pd nanoparticles or clusters ( Figure 4C ) ( He et al, 2022 ).…”
Section: Characterizations Of Single-atom Catalysts For Air Pollutant...mentioning
confidence: 99%